Maintenance of genetic and morphological identity in two sibling Syrrhopodon species (Calymperaceae, Bryopsida) despite extensive introgression. Issue 4 (21st July 2019) - Pereira, Marta R.; Ledent, Alice; Mardulyn, Patrick; Zartman, Charles E.; Vanderpoorten, Alain
Abstract: Bryophytes are a group of land plants in which the role of hybridization has long been challenged. Using genotyping by sequencing to circumvent the lack of molecular variation at selected loci previously used for phylogeny and morphology, we determine the level of genetic and morphological divergence and reproductive isolation between the sibling Syrrhopodon annotinus and S. simmondsii (Calymperaceae, Bryopsida) that occur in sympatry but in different habitats in lowland Amazonian rainforests. A clear morphological differentiation and a low (0.06), but significant F st derived from the analysis of 183 single nucleotide polymorphisms were observed between the two species. Conspecific pairs of individuals consistently exhibited higher average kinship coefficients along a gradient of geographic isolation than interspecific pairs. The weak, but significant genetic divergence observed is consistent with growing evidence that ecological specialization can lead to genetic differentiation among bryophyte species. Nevertheless, the spatial genetic structures of the two species were significantly correlated, as evidenced by the significant slope of the Mantel test based on kinship coefficients between pairs of interspecific individuals and the geographic distance separating them. Interspecific pairs of individuals are thus more closely related when they are geographically closer, suggesting that isolation‐by‐distance is stronger than the interspecific reproductive barrier and pointing to interspecific gene flow. We conclude that interspecific introgression, whose role has long been questioned in bryophytes, may take place even in species wherein sporophyte production is scarce due to dioicy, raising the question as to what mechanisms maintain differentiation despite weak reproductive isolation.